2023
DOI: 10.1038/s41419-023-05665-8
|View full text |Cite
|
Sign up to set email alerts
|

The MEF2A transcription factor interactome in cardiomyocytes

Abstract: Transcriptional regulators encoded by the Myocyte Enhancer Factor 2 (MEF2) gene family play a fundamental role in cardiac development, homeostasis and pathology. Previous studies indicate that MEF2A protein-protein interactions serve as a network hub in several cardiomyocyte cellular processes. Based on the idea that interactions with regulatory protein partners underly the diverse roles of MEF2A in cardiomyocyte gene expression, we undertook a systematic unbiased screen of the MEF2A protein interactome in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…Finally, it has been previously documented that there is an upregulation of MEF2A activity in cardiac hypertrophic conditions (Moustafa et al, 2023). Therefore, we hypothesized that the depletion of FOXP1 might enhance the hypertrophic cardiomyocyte phenotype due to derepression of MEF2A activity.…”
Section: Foxp1 Antagonizes Mef2a Transcriptional Activation Activitymentioning
confidence: 87%
See 3 more Smart Citations
“…Finally, it has been previously documented that there is an upregulation of MEF2A activity in cardiac hypertrophic conditions (Moustafa et al, 2023). Therefore, we hypothesized that the depletion of FOXP1 might enhance the hypertrophic cardiomyocyte phenotype due to derepression of MEF2A activity.…”
Section: Foxp1 Antagonizes Mef2a Transcriptional Activation Activitymentioning
confidence: 87%
“…In this MEF2A interactome study, we have identified a novel MEF2A binding protein, FOXP1, that negatively regulates MEF2A transcriptional activity during myogenesis and striated muscle maintenance. Previous research has begun to characterize the role of MEF2A in activating transcription for muscle-specific genes and cardiomyocyte survival (Moustafa et al, 2023). In addition, while MEF2 isoforms share a conserved MADS-box domain and MEF2 domain, the transactivation domain confers a wide range of specificity and function through post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the formation of costameres, an additional fundamental element, myocyte enhancer factor 2A (Mef2A), is involved [64]. Mef2A belongs to a family of transcription factors that regulate muscle differentiation, and it is crucial for maintaining structural integrity and supporting cell survival during the early stages of costamere differentiation [65]. Following positive regulation through FAK-mediated phosphorylation, Mef2A exerts transcriptional control over different genes encoding proteins localized within the cytoskeletal structure.…”
Section: Focal Adhesions and Cardiac Cell Differentiationmentioning
confidence: 99%